Infecção oral de neonatos de gerbils (Meriones unguiculatus) com taquizoítos de Neospora caninum - Ferreira, Maiara Sanitá Tafner (2014)
Neosporosis is a parasite disease caused by Neospora caninum protozoan and characterized as a major cause of abortion in cattle. Eventually is possible birth of animals with neurological signs, stillbirths or birth of clinically normal calves, but chronically infected. Although there are many researches related to bovine neosporosis, there are still doubts about the cycle and the pathogenesis of N. caninum infection, so that is suitable for certain control and prophylaxis strategies to disease. Gerbils are considered highly sensitive of the parasite replication. Thus, this study aimed to verify the occurrence of infection with N. caninum by oral inoculation of tachyzoites in gerbils (M. unguiculatus). Seventeen animals were orally inoculated with 4x105 N. caninum tachyzoites. The detection frequency of total DNA samples of N. caninum showed that the protozoan infectivity occurs via this route of inoculation, noting that 81.8 % of the inoculated animal parasite DNA was detected. In relation to tissues, it can be observed that the DNA parasite was found in all organs evaluated (heart, lungs, kidneys, liver, spleen, brain), by variable frequency, demonstrating the wide distribution of this parasite in animals tissues.